Deteksi gen pneumolysin (ply) Streptococcus pneumoniae pada Sampel Klinis Usia Lanjut secara Kultur dan PCR - Muthmainnah Muthmainnah; Mochammad Hatta; Muh. Nasrum Massi; Firdaus Hamid; Irawati Djaharuddin; Eddyman W Ferial; Andi Alfian Zainuddin; Mustika Hutabarat Sari (Poltekkes Kemenkes Bandung, 2020)
ABSTRACT Streptococcus pneumoniae, a gram-positive bacterium of normal flora but can be a pathogenic bacterium that causes pneumonia if the immune system declines. Community pneumonia ranks fourth and top ten diseases treated per year. Populations that are susceptible to pneumonia are children aged less than 2 years, old age. The Purpose aim to detect ply genes in sputum with suspected pneumonia in elderly as a virulence factor of S. pneumoniae by culture and PCR. This research method is a descriptive study to detect the virulence factor of the S. pneumoniae ply gene in the sputum of patients with suspected pneumonia in the elderly with the culture and PCR methods. Conventionally (culture method) obtained 1 sample from 56 positive samples of S. pneumoniae gram positive bacteria on the molecular method (PCR) there were 7 positive samples of S. pneumoniae bacteria from 56 samples. In detecting ply genes in sputum with suspected pneumonia in elderly as a virulence factor from S. pneumoniae bacteria were culturally detected 1 positive sample from 56 samples and by PCR method detected 7 positive samples from 56 samples. In detecting ply genes using culture and PCR it can be said that the PCR method is more accurate, fast and precise in detecting the S. pneumonia gene in sputum samples with suspected pneumonia in elderly.